Design Of Educational Game “Adventure Of A Sholeh Child” Using Adobe Flash Based On Android - Yohanda Oktaviary; Wahana, Aditya; Putri, Puji Handayani (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2024)
The material of the pillars of Islam is main the teachings of the Islamic religion guidelines for a person muslim . A number of schools and TPA and TPQ places convey material the with how teachers and children educate notice Then child educate repeat . This is assessed not enough efficient Approach This not enough effective use prevent boredom in children educate moment learn . Because that , is needed multimedia applications in the form of educational games Android based which contains material Pillars of Islam. Application This made using Adobe Flash CS6. The purpose of study is make educational game design " adventure " child pious " with Adobe Flash based android . For child under 10 years of age who will Study harmonious Islam . The data collection method used is bibliography , interviews , and observation . Design application methodical inbeetwen ( byframe ) .